The Company Valuation Market Methods - Dunal, Patryk (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
The company is a special form of investment. The validity of company valuation is a fact, that it allows to estimate the company value, and thus control the achievement of the basic objective of companies, which is the maximization of company value. Growing information needs led to the development of many methods, among which the most important division is the distinction between market and non-market methods. The purpose of this paper is to present market valuation methods to verify the hypothesis of the existence of a board subjectivity in commonly used procedure, which could lead to discrepancies in the final results. Procedure of market valuation consists of several steps: the selection of multipliers, the choice of the comparison group, the designation of the multipliers for the comparison group and their averaging, the calculation of the value measured at the company, and the adjustment of discount and bonuses. The presentation of this methodology should emphasize certain imperfections, and may be a proof of the validity of the hypothesis – the results carried out valuations of companies still differ from each other in a fairly large extent due to the arbitrariness and subjectivity of the selection of input data and the lack of consistency in the estimation of parameters. Moving the issue of market valuation methods is the impulse to discuss the valuation of companies, which in the future would lead to desired harmonize the methodology for estimating the basic parameters for the valuation, which undoubtedly will be an added value to the science of finance and management.